A Conceptual Commentary on Midrash Leviticus Rabbah: Value Concepts in Rabbinic Thought - Kadushin, Max (Brown Judaic Studies, 2020)
In this book Kadushin offers a running commentary on sections of Leviticus Rabbah. His goal is not only to explicate individual sections of this Late Antique midrashic work, but also to highlight the basic conceptual framework within which the rabbis worked. Kadushin's commentary highlights the indeterminacy of belief and the genuine emphatic trends that distinguish rabbinic Judaism while also calling attention to the special character of the rabbinic religious experience which he had earlier described as normal mysticism.